Pengaruh Temperatur dan Lama Pengepresan pada Alat Hot Press Pelepah Pinang - Sigit Kurniawan; Maizal Isnen; Alan Setiawan; Indra Wahyudi Legi (LPPM Politeknik Jambi, 2018)
The purpose of this study was to determine the effect of temperature and duration of pressing the Hot Press Tool on the quality of the mold for areca nut material. The method used is taking betel nut samples to be tested with temperature variations and length of pressing time. From this method, it is expected to have a significant effect on the results of the Hot Press Tool, because of the change in the properties of the material from the areca nut to temperature changes. The results showed that the temperature value had a significant effect on the press product with an optimum value of 120 0C, while the pressing time did not have enough effect on the quality of the mold. Of course this result is very instrumental in making automatic Hot Press Tools specifically used in products from areca nut.